Moringa oleifera as a potential bioactive agent against Gram-positive and negative bacteria: In-silico analysis of 1YN5 and 3RG1 receptor binding - CUT NILA THASMI; HAFIZUDDIN HAFIZUDDIN; HUSNURRIZAL HUSNURRIZAL; DASRUL DASRUL; AMALIA SUTRIANA; BASRI A. GANI; MUHAMMAD NAZAR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Thasmi CN, Hafizuddin H, Husnurrizal H, Dasrul, Sutriana A, Gani BA, Nazar M. 2024. Moringa oleifera as a potential bioactive agent against Gram-positive and negative bacteria: In-silico analysis of 1YN5 and 3RG1 receptor binding. Biodiversitas 25: 3411-3421. The natural antioxidant extract of Moringa oleifera Lam. simultaneously possesses anti-inflammatory, anti-infertility, antimicrobial, and antioxidant properties. This research aims to investigate the active chemical compounds isolated from the leaves of M. oleifera and examine the chemical interaction between the selected compounds and the 1YN5 and 3RG1 proteins based on the molecular docking model. M. oleifera leaves were collected from the Kajhu Village, District of Aceh Besar, Province of Aceh, Indonesia. The bioactive compounds were isolated through cold extraction by using the maceration technique. Chemical analysis and characterization of bioactive compounds were carried out by Fourier Transform Infrared Spectroscopy (FTIR) and Gas Chromatography-Mass Spectrometry (GC-MS). The antioxidant bioactivity/Free Radical Scavenging Potency (FRSP) was determined using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical assay. The molecular docking process refers to the modified MOE software docking protocol. The data obtained were analyzed descriptively. The ethanolic extract of M. oleifera leaf contains 38 bioactive compounds. Several bioactive compounds have high peak area percentages, including Oxirane, hexadecyl- (20.22%), TRICYCLO [20.8.0.0E7,16] TRIACONTA (14.35%), acetic acid (CAS), ethyl acetate (11.32%), n-Hexadecanoic acid (8.94%), and oleic acid (8.12%). Molecular docking showed that oleic acid, oxirane, hexadecyl, and 1-Heptacosanol have greater affinity to the 1YN5 gene, while octadecanoic acid and tetracontane have better binding affinity to the 3RG1 proteins. The bioactive compound 1-Heptacosanol bound both to the 1YN5 and 3RG1 proteins. The ethanolic extract of M. oleifera leaves possessed better IC50 (6.07 ppm), relatively twice lower when compared to the positive standard, Vitamin C (10.58 ppm). The M. oleifera ethanol extract exhibits antioxidant bioactivity in the very strong category. The bioactive compound 1-Heptacosanol shows binding affinity with both 1YN5 and 3RG1 proteins.